Integration of Correspondence and Coherence Theories: A Philosophical Approach to the Concept of Truth in Islam - Zain, Muhammad Fuad; Meidina, Ahmad Rezy; Roqib, Moh. (Interdisciplinary Journal of Social Science and Education (IJSSE), 2025)
Truth is a fundamental concept in philosophy and theology that has deep relevance in the Islamic tradition. This article examines the relevance of correspondence and coherence theories to the understanding of truth in Islam. Correspondence theory defines truth as the correspondence between propositions and external reality. In Islam, this approach is seen in revelation that is in harmony with natural reality as affirmed in many verses of the Qur'an. On the other hand, coherence theory emphasizes logical consistency in belief systems. Islam integrates revelation, reason, and sharia law to build a harmonious and rational belief. Truth in Islam is not only ontological, referring to the absolute reality of God, but also epistemological, encompassing the way humans understand and apply truth. The correspondence approach affirms the relationship of revelation to nature, while coherence ensures logical harmony within the belief system. The combination of the two creates a comprehensive framework, integrating spirituality, intellect and morality. The article concludes that the dialog between philosophical concepts and Islam enriches the understanding of the nature of truth, making it theologically and practically relevant in everyday life.